GAMBARAN PENGETAHUAN DAN SIKAP IBU HAMIL TERHADAP SENAM HAMIL DI PUSKESMAS RAWASARI KOTA JAMBI TAHUN 2008 - Siti Aisyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2008)
Pregnant gymnastics is a movement excercise therapy for pergnant women. This therapy is aimed at preparing women physically as well as mentally for quic, safe and spon tenous delivery, Research in PUSKESMAS of Rawasari of Jambi City shows that women’s picture of pregnant gymnastics is 59 %, their knowledge 71,7 % and their attitude 61,55%. Despite the fact that many women do not  prctice pregnant gymnastics, PUSKESMAS functionaries keep educating them about the importance of pregnant gymnastics for baby delivery process. Key word : Pregnant gymnastics, knowledge , attitude